Sonochemiluminescence of Melatonin quenched by luminol in an aqueous solution - R, Khoroljav; T, Badamkhatan; B, Duurenbuyan; A.M, Abdrakhmanov; G.L, Sharipov (Scientific transaction of the National University of Mongolia. Physics, 2022)
Melatonin, a hormone of the pineal gland, that plays an important role in energy metabolism and regulation of physiological of the human body, effectively quenches luminol chemiluminescence and sonochemiluminescence in an aqueous solution. The Stern-Volmer quencher rate coefficient has been determined. The detection limit of melatonin in the solution for the effective quenching of luminol sonochemiluminescence is 20 ng/ml.